2014
DOI: 10.1371/journal.pone.0099245
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor α Activation Induces Hepatic Steatosis, Suggesting an Adverse Effect

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic triglyceride accumulation, ranging from steatosis to steatohepatitis and cirrhosis. NAFLD is a risk factor for cardiovascular diseases and is associated with metabolic syndrome. Antihyperlipidemic drugs are recommended as part of the treatment for NAFLD patients. Although fibrates activate peroxisome proliferator-activated receptor α (PPARα), leading to the reduction of serum triglyceride levels, the effects of these drugs on NAFLD remain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 45 publications
6
50
2
Order By: Relevance
“…Stimulated de novo lipogenesis has been observed after treatment with PPAR-a agonists in many experiments (24,25). In the 6-week short-term drug administration experiment, we did observe that fenofibrate significantly up-regulates the expression level of SCD-1 and SREBP-1c mRNA in the rat liver as the previous studies have been shown.…”
Section: Discussionsupporting
confidence: 77%
“…Stimulated de novo lipogenesis has been observed after treatment with PPAR-a agonists in many experiments (24,25). In the 6-week short-term drug administration experiment, we did observe that fenofibrate significantly up-regulates the expression level of SCD-1 and SREBP-1c mRNA in the rat liver as the previous studies have been shown.…”
Section: Discussionsupporting
confidence: 77%
“…This inconsistency with our study could be related to the shorter feeding time of only 2 weeks of the high-fructose diet and fenofibrate administration [10]. Another report found that hepatic steatosis was induced after male C57BL/6J mice were directly administered with fenofibrate through daily gavage for 10 days.…”
Section: Discussioncontrasting
confidence: 87%
“…Fenofibrate, a specific agonist of PPARα, represents the most frequently used clinical drug for decreasing hypertriglyceridemia and obesity. Several experimental observations indicate that activation of PPARα could prevent hepatic triglyceride (TG) accumulation and could have a therapeutic effect against NAFLD [6], but the precise mechanism of this drug in ER stress has not yet been fully elucidated in the NAFLD liver [7,8], and there has even been some inconsistency [9,10]. Therefore, it is necessary to study whether fenofibrate treatment influences ER stress and which pathway it uses in the NAFLD liver.…”
Section: Introductionmentioning
confidence: 99%
“…As signs of incomplete oxidation are exacerbated by fenofibrate, long term treatment could be ineffective, or even aggravate hepatic metabolic dysfunction, as was also proposed [52].…”
Section: Discussionmentioning
confidence: 93%
“…Fibrates have been proposed in the treatment of NAFLD but some authors found a negative outcome [52]. As signs of incomplete oxidation are exacerbated by fenofibrate, long term treatment could be ineffective, or even aggravate hepatic metabolic dysfunction, as was also proposed [52].…”
Section: Discussionmentioning
confidence: 99%